The influence employability of vocational students through internship experiences and 21st-century competencies: a moderated mediation model - Didi Pianda; Hilmiana; Sunu Widianto; Dina Sartika (Cogent Education)
Using the social cognitive theory, this study examines the mediation role of 21st-century competencies in the relationship between student internship sxperience and employability of vocational students and the role of moderation of psychological capital on the relationship between SIE and 21stCE. This study aims to analyse the employability of vocational students through internship experience and 21st century competencies through a moderated mediation model. This study collected data through a direct survey of 266 vocational students in Aceh Province. SPSS V.25 and SmartPLS 4.1.0.3 are used to test the proposed hypothesis. The findings revealed that SIE positively increased EVS through the 21stCE. Further research shows that the effect of SIE on 21stCE is more significant for students with high PsyCap than for low PsyCap. This study expands the existing literature on the relationship between SIE and EVS by integrating SCT from the perspective of vocational education. These findings offer valuable insights and guidance for policymakers for education management regarding how and when SIE leads to better EVS among vocational students. This is one of the pioneering empirical studies highlighting SIE’s importance to EVS among vocational students in the developing Aceh Province in Southeast Asia. In addition, the study confirms that 21st-century competencies play an essential role in explaining how SIE drives EVS.